An Extremum Seeking Scheme with Global Convergence Properties. Issue 14 (2021) - Mimmo, N.; Marconi, L.; Nortarstefano, G.
Abstract: The paper presents an extremum seeking-based optimisation algorithm guaranteeing global convergence to an arbitrary small neighbourhood of the optimum. We present a modification of canonical solutions present in literature yielding semiglobal and practical convergence by overtaking the need to know the set of initial conditions for tuning the design parameters. A comparison with existing solutions and numerical results are also presented to highlight the main features of the proposed algorithm.